The Effect of Nipple Stimulation on the Acceleration of Cervical Dilation in Primigravida Mothers in the First Stage of Labor Active Phase - Sri Wulan; Dea Febriani; Rita Junia; Nurulhikmah (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2025)
Labor is a physiological process involving the coordination of uterine contractions, cervical dilation, and fetal descent through the birth canal. One of the factors that can prolong the duration of labor is the slow process of cervical dilation due to low levels of natural oxytocin. A non-pharmacological method that can stimulate the release of endogenous oxytocin is nipple stimulation, which has the potential to accelerate cervical dilation and facilitate the progress of labor. This study aimed to analyze the effect of nipple stimulation on the acceleration of cervical dilation in primigravida mothers during the first stage of active labor. The research employed a quasi-experimental design with two groups: an intervention group (nipple stimulation) and a control group (no stimulation). The study was conducted at X Maternity Clinic from July to September 2025 with a total of 12 respondents randomly divided into two groups of six participants each. Data were analyzed using the independent t-test with a significance level of α = 0.05. The results showed that the mean duration of full cervical dilation in the intervention group was 4.2 hours (SD = 0.8), while in the control group it was 6.1 hours (SD = 1.0) with a p-value of 0.011. The mean rate of cervical dilation in the intervention group was 1.8 cm/hour (SD = 0.4), higher than in the control group at 1.1 cm/hour (SD = 0.3) with a p-value of 0.017. It can be concluded that nipple stimulation significantly affects the acceleration of cervical dilation in primigravida mothers during the active phase of the first stage of labor. This intervention serves as a safe, effective, and easily applicable non-pharmacological alternative to support the normal progress of labor.